2013
DOI: 10.1093/pcp/pct144
|View full text |Cite
|
Sign up to set email alerts
|

Fructan Metabolism in Developing Wheat (Triticum aestivum L.) Kernels

Abstract: Although fructans play a crucial role in wheat kernel development, their metabolism during kernel maturation is far from being understood. In this study, all major fructan-metabolizing enzymes together with fructan content, fructan degree of polymerization and the presence of fructan oligosaccharides were examined in developing wheat kernels (Triticum aestivum L. var. Homeros) from anthesis until maturity. Fructan accumulation occurred mainly in the first 2 weeks after anthesis, and a maximal fructan concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 62 publications
5
62
1
1
Order By: Relevance
“…This behavior contrasts with that in total wheat grains, where the highest concentrations of 1-kestose and nystose have been detected before the onset of starch accumulation (Verspreet et al, 2013c). The quantities of 6-kestose and bifurcose (levan-and graminan-type) declined in both the cavity and in the whole grain, consistent with observed spatio-temporal transcript profiles of the genes encoding (A) Scheme of a half-sectioned barley grain at storage stage with enlargement of tissues responsible for nutrient transfer into the endosperm.…”
Section: Discussion Distinct Patterns Of Oligosaccharide Distributioncontrasting
confidence: 81%
“…This behavior contrasts with that in total wheat grains, where the highest concentrations of 1-kestose and nystose have been detected before the onset of starch accumulation (Verspreet et al, 2013c). The quantities of 6-kestose and bifurcose (levan-and graminan-type) declined in both the cavity and in the whole grain, consistent with observed spatio-temporal transcript profiles of the genes encoding (A) Scheme of a half-sectioned barley grain at storage stage with enlargement of tissues responsible for nutrient transfer into the endosperm.…”
Section: Discussion Distinct Patterns Of Oligosaccharide Distributioncontrasting
confidence: 81%
“…Genotype DHTW-60, HD-2967, WH-1105 and HTW-11 was found maximum in yield per square meter (Table 4) under drought situation with delayed sowing. Similar findings have also been reported by various workers (Verspreet, 2015;Munjal & Dhanda, 2016;Zampieri et al, 2017;andRam et al, 2017a, 2017b). Dwivedi et al, (2017) also reported higher reduction in grain yield (60.3%).…”
Section: Mean Sum Of Squaresupporting
confidence: 90%
“…In the generative phase and during kernel development, fructans synthesized and accumulated in shoots are remobilized to supply kernels with additional sucrose (Amiard et al 2003;Zhang et al 2015). Fructans (like 1-kestose) present in immature kernels are used up during starch synthesis during reserve accumulation (Verspreet et al 2013;Peukert et al 2014). In mature cereal kernels, 1-kestose (a-D-glucopyranosyl-(1 ?…”
Section: Introductionmentioning
confidence: 99%